1976
DOI: 10.1002/bbpc.19760800506
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of Biologically Important Transition Metal Complexes. I. Cyanocobalamin and Related Corrin Complexes of Rhodium(III)

Abstract: Bei den in dieser Zeitschrift wiedergegebenen Gebrauchsnamen, Handelsnamen, Warenbezeichnungen und dgl handelt es sich häufig um gesetzlich geschützte eingetragene Warenzeichen, auch wenn sie nicht als solche mit ® gekennzeichnet sind. Photochemistry of Biologically Important Transition Metal Complexes. I. Cyanocobalamin and Related Corrin Complexes of Rhodium(III)A. Vogler, R. Hirschmann, H. Otto, and H. KunkelyInstitut für Chemie, Universität Regensburg, 8400 Regensburg, GermanyAbsorptionsspektren, sichtbar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0
1

Year Published

1976
1976
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 16 publications
2
22
0
1
Order By: Relevance
“…The CN group attached to Co 3+ in the tetrapyrrolic corrin macrocyclic ring in B 12 is replaced by an OH group in B 12b . B 12 undergoes photolysis to B 12b in aqueous solution which is degraded to irreversible oxidation products (6)(7)(8)(9)(10)(11). Similar reactions occur on the chemical degradation of B 12 and B 12b in the presence of ascorbic acid (AH 2 ) (12)(13)(14) and may be expressed as follows: The effect of thiamine (15,16), nicotinamide (17,18), and riboflavin (19)(20)(21)(22) on the photolysis of B 12 and B 12b has been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The CN group attached to Co 3+ in the tetrapyrrolic corrin macrocyclic ring in B 12 is replaced by an OH group in B 12b . B 12 undergoes photolysis to B 12b in aqueous solution which is degraded to irreversible oxidation products (6)(7)(8)(9)(10)(11). Similar reactions occur on the chemical degradation of B 12 and B 12b in the presence of ascorbic acid (AH 2 ) (12)(13)(14) and may be expressed as follows: The effect of thiamine (15,16), nicotinamide (17,18), and riboflavin (19)(20)(21)(22) on the photolysis of B 12 and B 12b has been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Cyanocobalamin seems to be an exception. Evidence was obtained that the photoaquation of cyanocobalamin is initiated by excited ligand field states [7,8]. Generally, the identification of reactive excited states of cobalamins is hampered by the fact that their absorption spectra are dominated by the intense rr* intraligand bands of the corrin ligand.…”
Section: Introductionmentioning
confidence: 99%
“…It has been recently shown that the photoaquation of cyanocobalamin originates from an excited LF state 26 . It seems that generally the photochemistry of cobalamins is closely related to that of other transition metal complexes and particularly to the photochemical reactions of pentacyano complexes of Co(III) 26 .…”
Section: J F Endicott "Concepts In Inorganic Photomentioning
confidence: 99%
“…It seems that generally the photochemistry of cobalamins is closely related to that of other transition metal complexes and particularly to the photochemical reactions of pentacyano complexes of Co(III) 26 .…”
Section: J F Endicott "Concepts In Inorganic Photomentioning
confidence: 99%